Implementasi Metode Mind Mapping Pada Mata Pelajaran Akidah Akhlak Kelas Viii Di Mtss Pondok Pesantren Riadhus Sholihin Kabupaten Sijunjung - Eflin Farera; Charles; Pendi Hasibuan; Salmi Wati (KOLONI, 2022)
This research is motivated by the fact that students are less able to communicate various ideas and ideas, especially in the field of note-taking. Second, students are confused about where to start when they have to convey their ideas or ideas, which causes students to be less active and productive in class because they store all ideas and ideas in their minds. This study uses a descriptive qualitative approach. Collecting data in this study researchers obtained through observation and interviews. This study uses 3 informants, namely teachers, students, and informants supporting the principal. The data analysis technique that the researchers carried out was data reduction, data presentation and data verification. To ensure the validity of the research data, the researchers conducted data trigulation. Based on the results of the study, it can be understood that the Mind Mapping method is the right method for learning that is oriented to the development of creativity and learning motivation for students. The teacher provides a stimulus to students in the form of a unique and fun learning method so that in class VIII learning can provide its own benefits for students, especially in learning Akidah Akhlak.  Keywords: Method, Mind Mapping, Akidah Akhlak